Coparenting and Parental Involvement During School Transition Among Chinese Mothers and Fathers: Children’s School Liking as a Moderator - Tao, Sisi; Lau, Eva Yi Hung (Frontiers in Psychology, 2021)
Parental involvement is a vital social resource that helps children to deal with different challenges in their learning and development in the transition period and may be a strong determinant of children’s outcomes. While the role of fathers has been increasingly recognized, there has been a lack of studies examining the predictive role of mother and fathers’ coparenting to parental involvement and child readiness outcomes. The purpose of this study is to examine the longitudinal association between coparenting behavior and parental involvement for parents with children in the transition to primary school in a Chinese context, and test whether children’s school liking moderated these associations. Using stratified random sampling, 324 children (Mage=70.57months, female=51%) and their parents from 10 kindergartens in Hong Kong participated in the study. Both mothers and fathers provided information about their spouse’s coparenting behavior at Time 1 (the final year of kindergarten), and their parental involvement at home and school at Time 1 and 2 (the first year of primary school). Children’s school liking was assessed by puppet interview at Time 1. Results indicated that maternal cooperation was positively associated with paternal involvement at home and in school, and paternal cooperation was positively associated with maternal involvement at home. Children’s school liking moderated the longitudinal associations between coparenting behavior (Time 1) and parental involvement (Time 2). Specifically, mothers of children with high levels of school liking were involved more in school when they perceived more cooperation from the spouse. Fathers of children with low levels of school liking were less involved in school when they perceived more cooperation, while involved more at home and in school when they perceived more triangulation from the spouse. Additionally, fathers perceiving more triangulation decreased their home involvement when the child reported high levels of school liking. Findings of this study revealed that coparenting, children’s school liking, and parental gender might be important to understanding parental involvement during school transition.